Heavy metal contamination during processing of canned fish: a review on food health and food safety - Md. Masud, Rana; Roslianah, Asdari; Ahmed Jalal Khan, Chowdhury; Mohammad Bodrul, Munir (Desalination Publications, 2023)
Fish in cans is more popular than ever because of its convenience, improved quality, less risk of contamination, and long shelf life. To preserve seafood products, the canning process uses a hermetic closure and thermal techniques. Tuna, salmon, mackerel, and herring are a few marine fish species that are widely used in canned goods. The canning procedure has significant shortcomings. Problems with canning include the transfer of hazardous metals from the cans into the food, incorrect canning, which can cause botulism, and chemical contamination. The biggest and most pervasive issue is the presence of heavy metals like Pb, Hg, Cd, Cu, and Zn in canned fish. These metals are exceedingly poisonous, persistent, and difficult to biodegrade even at low concentrations. Heavy metals significantly affect marine bioaccumulation, toxicity, and water contamination. Heavy metals build up in marine fish along the food chain as a result of growing industrial and agricultural environmental harm, and they are eventually absorbed by humans through canned foods. While Pb and Cd toxicity can result in renal, cardiovascular, and reproductive issues, heavy metal (Hg) toxicity can lead to eye impairment, vertigo, and a weakened immune system. So that consumers may learn more and make wise decisions about consuming canned fish, the main method by which heavy metal contamination in canned fish spreads could be identified in this review paper.